Plant kin : a multispecies ethnography in indigenous Brazil - Miller, Theresa L. (Theresa Lynn), 1985- (Louann Atkins Temple women & culture series ;, 2019)
"The Indigenous Canela inhabit a vibrant multispecies community of nearly 3,000 people and over 300 types of cultivated and wild plants living together in Maranhão State in the Brazilian Cerrado (savannah), a biome threatened with deforestation and climate change. In the face of these environmental threats, Canela women and men work to maintain riverbank and forest gardens and care for their growing crops, whom they consider to be, literally, children. This nurturing, loving relationship between people and plants--which offers a thought-provoking model for supporting multispecies survival and well-being throughout the world--is the focus of Plant Kin. Theresa L. Miller shows how kinship develops between Canela people and plants through intimate, multi-sensory, and embodied relationships. Using an approach she calls "sensory ethnobotany," Miller explores the Canela bio-sociocultural life-world, including Canela landscape aesthetics, ethnobotanical classification, mythical storytelling, historical and modern-day gardening practices, transmission of ecological knowledge through an education of affection for plant kin, shamanic engagements with plant friends and lovers, and myriad other human-nonhuman experiences. This multispecies ethnography reveals the transformations of Canela human-environment and human-plant engagements over the past two centuries and envisions possible futures for this Indigenous multispecies community as it reckons with the rapid environmental and climatic changes facing the Brazilian Cerrado as the Anthropocene epoch unfolds"--